Parent Involvement in the Program for Developing of Children's Emotional Social Values in Darussalam Kindergarten of Sugihwaras Sidoarjo - Masfufah, Siti; Darminto, Eko; Naqiyah, Najlatun (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the forms of emotional, social values of children aged 5-6 years and their implementation with a parent engagement program. The subject of research children aged 5-6 years group B in the Sugihwaras kindergarten in Sidoarjo Temple with a total of 7 children and their parents. The research approach used is qualitative data collection techniques through observation, documentation, and interviews and field notes as well as the use of Cresswell's data analysis which is processing data and preparing data for analysis, reading all data, coding data, applying the results of the coding process and finally describe the results of the data during the study. The findings of this study will be tested for truth by using triangulation techniques. The findings of this study indicate the results that the Parental Involvement in the Children's Emotional Social Value Program in TK Darussalam Sugihwaras Sidoarjo Temple is carried out through the social-emotional value program by involving parents in the TK institution. Parental support has benefits and a big contribution to the education of their children. Throughout bonding activities, cooking classes, parenting, curriculum preparation, habituation activities at home, and modeling to develop children's emotional values according to their age stages and abilities. The involvement of parents in children's emotional, social value programs at every school institution should be fully socialized. Given the participation of parents is needed in the child's emotional, social process. Support, appropriate stimulation, and opportunities to explore children can grow and develop good social-emotional values of children.